A novel two‐dimensional preparative chromatography method designed for the separation of traditional animal Tibetan medicine Osteon Myospalacem Baileyi. Issue 21 (23rd September 2014) - Jiang, Lei; Tao, Yanduo; Wang, Dan; Tang, Chuchen; Shao, Yun; Wang, Qilan; Zhao, Xiaohui; Zhang, Yaozhou; Mei, Lijuan
<x xml:space="preserve">Abstract</x> Animal medicine is an important part in traditional Tibetan medicine. However, information about the chemical composition of animal medicine is very limited, and there is a lack of comprehensive chromatographic purification methods. In the present work, animal medicine Osteon Myospalacem Baileyi was taken as an example and a novel two‐dimensional preparative chromatographic method was established for the preparation of single compounds with high purity from the extract of Osteon Myospalacem Baileyi. The first‐dimension preparation was carried on a DAISO Silica prep column, and ten fractions were obtained from the 112.3 g crude sample within 12 injections. A diol prep column used in nonaqueous mobile phase was selected for the second‐dimension preparation. The purity of the compounds isolated from the crude extract was >98%, which indicated that the method built in this work was efficient to manufacture single compounds of high purity from the extract of Osteon Myospalacem Baileyi. Additionally, this method showed great potential in the purification of weakly polar chemicals and it could act as a good example in the purification of other traditional animal medicines.